Constitutional and legal guarantees and limitations of the Federal Public Service Council - Hussein Najem , Ameen; Zaki Nuri , Assist.prof.Suha (Basra studies journal, 2022)
The Iraqi constitutional legislator defined the federal authorities with three powers, namely (executive, legislative, and judicial) in accordance with the text of Article (47) of the Constitution of the Republic of Iraq for the year 2005, and created bodies and institutions of an independent nature. Some of them existed previously before the establishment of this constitution, and others created them according to constitutional texts and referring their formation and regulation of their work by law. And, among these bodies (the Federal Public Service Council) the legislator has been granted legal personality and financial and administrative independence. It is necessary to find real guarantees to support the work of the Council and for the purpose of translating the privileges granted by the legislator to the Council, as well as creating restrictions and a relationship between the Council and other authorities, to ensure the legal unity of the state.